2016
DOI: 10.2174/1570179413666151218204056
|View full text |Cite
|
Sign up to set email alerts
|

Potassium 4-Iodylbenzenesulfonate (PIBS): An Efficient Recyclable Hypervalent Iodine Reagent for Iodo-functionalization of Alkenes, Alkynes and Ketones

Abstract: Potassium 4-iodylbenzenesulfonate (PIBS) is a thermally stable and water soluble hypervalent iodine oxidant particularly useful as a recyclable reagent for oxidative iodination of alkenes, alkynes and ketones. This reagent can be effectively recovered from the reaction mixture by treatment of the aqueous layer with Oxone at 60 o C followed by filtration of the precipitate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…93 Zhdankin et al also reported the synthesis of the recyclable and water-soluble I(V) reagent potassium 4-iodylbenzenesulfonate (PIBS) (204) via the oxidation of 4-iodobenzenesulfonic acid using Oxone ® in water. 94 This watersoluble reagent can be used for the oxidative iodination of arenes, 94 alkenes, 95 alkynes, 95 and ketones 95 (Scheme 40). Unreacted PIBS (204) and its reduced form PIBS-H can be recovered from the reaction mixture.…”
Section: Recyclable Non-polymeric Hypervalent Iodine(v) Reagentsmentioning
confidence: 99%
See 4 more Smart Citations
“…93 Zhdankin et al also reported the synthesis of the recyclable and water-soluble I(V) reagent potassium 4-iodylbenzenesulfonate (PIBS) (204) via the oxidation of 4-iodobenzenesulfonic acid using Oxone ® in water. 94 This watersoluble reagent can be used for the oxidative iodination of arenes, 94 alkenes, 95 alkynes, 95 and ketones 95 (Scheme 40). Unreacted PIBS (204) and its reduced form PIBS-H can be recovered from the reaction mixture.…”
Section: Recyclable Non-polymeric Hypervalent Iodine(v) Reagentsmentioning
confidence: 99%
“…Unreacted PIBS ( 204 ) and its reduced form PIBS-H can be recovered from the reaction mixture. 94 95…”
Section: Non-polymeric Recyclable Hypervalent Iodine Reagentsmentioning
confidence: 99%
See 3 more Smart Citations